Social Historical Psychology: Historicity X Naturalization, Theoretical – Practical Challenges of Production in Public Health - Peters Kahhale, Edna; de Castro e Silva, Carlos Roberto; da Silva, Alexandro (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2014)
It aims to promote critical debate on the construction of knowledge in psychology taking parameters such as the notion of historicity , the question of dialectical objectivity - subjectivity the constitution of the subject and subjectivity from the perspective of dialectical and historical materialism . Question the knowledge of psychology from category involves questioning the historicity of individual naturalization, natural phenomena and located in a social perspective. That research perspective and reflection pursues the foundations of theoretical constructs and practice, opening a field of reflection on the interweaving of concrete social practices and theoretical constructs generated from demands in specific contexts (situations of health and illness; production of material life, estrangement and unusual or hegemonic meanings opposite the everyday life). The problematic of the inclusion of psychology in primary and secondary care is discussed of both point of view theoretical as an action.